2020
DOI: 10.26881/rgtn.2020.07
|View full text |Cite
|
Sign up to set email alerts
|

Wpływ pandemii COVID­­‑19 na pomorski rynek pracy

Abstract: W artykule podjęto próbę oceny wpływu pandemii COVID­­‑19 na pomorski rynek pracy. Autor analizuje zmiany poszczególnych wskaźników opisujących sytuację na pomorskim rynku pracy oraz omawia trudności, z jakimi w sferze zawodowej w wyniku pandemii borykają się przedstawiciele szczególnych grup na rynku pracy – kobiety i osoby młode. Wnioski wskazują na negatywny wpływ pandemii COVID­­‑19 na regionalny rynek pracy i zatrudnienie, a z negatywnymi konsekwencjami przyjdzie mierzyć się jeszcze długo po ustaniu pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The decided majority of research into the effects of the COVID-19 pandemic on the labor market are based exclusively on resource analysis, omitting stream analysis [Jones et al, 2020;Radlińska, 2020;Rutkowski, 2020]. Meanwhile, analysis of the position of individuals on the labor market in the past allows for prediction of their various positions on the market in the future (i.e., the possibility of staying in a defined state or a change of state).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The decided majority of research into the effects of the COVID-19 pandemic on the labor market are based exclusively on resource analysis, omitting stream analysis [Jones et al, 2020;Radlińska, 2020;Rutkowski, 2020]. Meanwhile, analysis of the position of individuals on the labor market in the past allows for prediction of their various positions on the market in the future (i.e., the possibility of staying in a defined state or a change of state).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has shown that after a decline in jobs across the economy as a result of the economic lockdown in the early phase of the pandemic, there was a clear recovery on the labor market. Changes to the labor market in Poland after the outbreak of the COVID-19 pandemic have been broadly described in the literature [GUS, 2020;Radlińska, 2020;Rutkowski, 2020]. However, this research has been limited to resource analysis, that is to say, analysis using economic quantities in the form of resources.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of employees and employers during the pandemic and its effect on the economic situation of the population [32][33][34][35];…”
mentioning
confidence: 99%